Bad blood : a Henry Christie thriller - Oldham, Nick, 1956- (Oldham, Nick, 1956- Detective Superintendent Henry Christie novel., 2017)
As former Detective Superintendent Henry Christie settles into a new life running The Tawny Owl pub with his fiancée Alison, their rural idyll is disrupted by a violent intruder. After Henry foils a kidnap attempt on Alison's daughter, it becomes clear that he and his family have become the targets of a ruthless professional killer. But who... and why?